Bias Toward Drug-Related Stimuli Is Affected by Loading Working Memory in Abstinent Ex-Methamphetamine Users - Deldar, Zoha; Ekhtiari, Hamed; Pouretemad, Hamid Reza; Khatibi, Ali (Frontiers in Psychiatry, 2019)
Background: There is a trade-off between drug-related impulsive process and cognitive reflective process among ex-drug abusers. The present study aimed to investigate the impulsive effects of methamphetamine-related stimuli on Working Memory (WM) performance by manipulating WM load in abstinent ex-methamphetamine users. Methods: Thirty abstinent ex-methamphetamine users and thirty non-addict matched control participants were recruited in this study. We used a modified Sternberg task in which participants were instructed to memorize three different sets of methamphetamine-related and non-drug related words (3, 5, or 7 words) while performing a secondary attention-demanding task as an interference. Results: Repeated measures analysis ANOVA revealed that reaction times of abstinent ex-methamphetamine users increased during low WM load (3 words) compared to the control group (p=0.01). No significant differences were observed during high WM loads (5, 7 words) (both p’s >0.1). Besides, reaction times of the experimental group during trials with high interference (3, 5, 7 words) was not significantly different compared to the control group (p>0.2). Conclusion: These findings imply that increasing WM load may provide an efficient buffer against attentional capture by salient stimuli (i.e., methamphetamine-related words). This buffer might modify the effect of interference bias. Besides, presenting methamphetamine-related stimuli might facilitate the encoding phase due to bias towards task-relevant stimuli. This finding has an important implication, suggesting that performing concurrent demanding tasks may reduce the power of salient stimuli and thus improve the efficiency of emotional regulation strategies.